Exploring young women's constructions of love and strategies to navigate violent relationships in South African informal settlements. Issue 11 (2nd November 2019) - Willan, Samantha; Ntini, Nolwazi; Gibbs, Andrew; Jewkes, Rachel
Abstract: This paper explores young women's experiences and constructions of love-relationships and intimate partner violence in South Africa, and the role of agency in women's decisions to remain in or leave violent love-relationships. Understanding why young women stay in or leave violent love-relationships is key to developing nuanced understandings of agency and informing intimate partner violence prevention interventions. Data were collected from 15 young women in informal settlements in eThekwini Municipality, South Africa, via in-depth interviews, photovoice and participant observation, and were analysed inductively. While women's love-relationships were frequently violent, they often stayed in them for long periods, usually because the relationships met other important aspirations, including the desire for respect and dignity. Nonetheless, many women left when they no longer felt loved and respected, which they believed was shown by men's behaviours, specifically: indiscreet affairs; not spending time together; not spending money on her and any child(ren); and public (and humiliating) violence. Emotional and economic support from families also influenced women's decisions about leaving or staying. These data demonstrate that agency goes beyond definitive acts of leaving violent relationships; rather it is fluid, contested and contextual, with many factors influencing young women's goals and actions.